SERVICE SECTOR: HOW TO FORM A COMPETITIVE ENVIRONMENT - Toxirova , Gavxaroy Tolibjon qizi (Innovative Development in Educational Activities, 2023)
The reforms carried out in our country created the basis for the development of all sectors of the economy, including the service sector. It remains urgent to improve the mechanisms for the development of the service sector based on the internal capabilities of our country. Formation of a competitive environment in the service sector in the context of modernization of the economy and improvement of population welfare is one of the important issues facing the country’s economy today. In particular, aspects such as determining the perspective of creating a competitive environment in the service sector, which is recognized as the main driving force of ownership, improving organizational and economic mechanisms, and developing scientifically based proposals and practical recommendations on this issue, are studied in the article.